Innovation of Cooling System Learning Media Android-Based Air Using Smart Apps Creator for Vocational High School Students - Andri Setiyawan; Rizal Alvindo; Arief Kurniawan; Lena Citra Manggalasari (Universitas Ahmad Dahlan, 2023)
This study aims to develop Android-based cooling system maintenance learning media using Smart Apps Creator, determine the feasibility and effectiveness of the media, and determine students' responses after using the learning media that has been developed. This research is a type of research and development developed using the ADDIE development model. The resulting product is an Android application made using Smart Apps Creator. Product trials were carried out using a one-group pretest-posttest design, while the instruments used were questionnaires and test instruments. The results of this study are that this learning media gets